F02 Cognitive And Oculomotor Performance In Premanifest Huntington Disease: One-year Follow-up. (17th September 2014) - Júlio, F; Caetano, G; Januário, C; Castelo-Branco, M
Abstract : Background: Cognitive and oculomotor performance have been extensively studied in Huntington Disease (HD), but evidence for significant deficits in premanifest gene carriers is still controversial. Moreover, their role as markers of disease status and progression is not yet convincingly established. Aims: This study aims to understand the evolution of neuropsychological and saccadic performance in premanifest HD (preHD) over a course of 3 years. The results of the baseline assessment and preliminary longitudinal data regarding the one-year follow-up visit of the preHD group are shown here. Methods: 15 preHD participants and 22 controls completed the baseline assessment. 10 preHD participants have completed the second visit so far. A comprehensive neuropsychological test battery was used to evaluate the overall cognitive functioning of the participants. An experimental paradigm was designed to assess oculomotor function. Participants completed four different horizontal saccadic tasks with an increasing executive/memory load: prosaccade, antisaccade, 1-or-2 back memory prosaccade and antisaccade. Success rate (percentage of error free trials), latency, directional and timing errors were calculated. Results: No significant differences were found between preHD and controls in any of the neuropsychological tests, suggesting a similar overt cognitive baseline at visit #1. The cognitive results of the preHD group at visits #1 and #2 showed that their performance improved in some of the tests used. Concerning saccadic parameters, the preHD group exhibited at baseline a significantly faster response time compared to controls, specifically in memory antisaccades. At visit #2, preHD participants showed a lower success rate and an increased latency, particularly in tasks involving inhibitory processes. Conclusions: These data suggest that oculomotor performance of the preHD group may rely on more automatic responses when an executive/memory load is added to the task, deteriorates in time, and also that temporal saccade properties can mark the presence of early neurodegeneration in HD. Furthermore, despite an already evident decline in the saccadic performance of preHD individuals after one year, this is not paralleled by overt cognitive deficits as measured by conventional neuropsychological tests.